Reducing Handoff Blocking Probability in Wireless Cellular Networks- A Review - Fatma Siddiqui, Ambreen; Kumar, Pankaj; Gaurang Tiwari, Raj (International Journal of Computer Sciences and Engineering, 2025)
The continuity of service in an active cell is one of the most important issues in wireless cellular networks. Blocking occurs when a base station has no spare channel to allocate to a mobile user. It can be either new call blocking or handoff call blocking. In this paper, a review is given to better understand handoff blocking probability reducing models. These models prevent dropping of calls and improve quality of service.